Micronutrient deficiencies in children with coeliac disease; a double-edged sword of both untreated disease and treatment with gluten-free diet. Issue 5 (May 2021) - McGrogan, Lorcan; Mackinder, Mary; Stefanowicz, Fiona; Aroutiounova, Maria; Catchpole, Anthony; Wadsworth, John; Buchanan, Elaine; Cardigan, Tracey; Duncan, Hazel; Hansen, Richard; Russell, Richard K.; Edwards, Christine A.; et al.
Summary: Introduction: In coeliac disease (CD) micronutrient deficiencies may occur due to malabsorption in active disease and diminished intake during treatment with a gluten-free diet (GFD). This study assessed the micronutrient status in children with CD at diagnosis and follow-up. Methods: Fifteen micronutrients were analysed in 106 blood samples from newly diagnosed CD and from patients on a GFD for <6 months, 6–12 months and with longstanding disease (>12 months). Predictors of micronutrient status included: demographics, disease duration, anthropometry, gastrointestinal symptoms, raised tissue transglutaminase antibodies (TGA), multivitamin use and faecal gluten immunogenic peptide (GIP). Micronutrient levels were compared against laboratory reference values. Results: At CD diagnosis (n = 25), low levels in ≥10% of patients were observed for: vitamins E (88%), B1 (71%), D (24%), K (21%), A (20%) and B6 (12%), ferritin (79%), and zinc (33%). One year post-diagnosis, repletion of vitamins E, K, B6 and B1 was observed (<10% patients). In contrast, deficiencies for vitamins D, A and zinc did not change significantly post-diagnosis. Copper, selenium and magnesium did not differ significantly between diagnosis and follow-up. All samples for B2, folate, vitamin C (except for one sample) and B12 were normal. A raised TGA at follow-up was associated with low vitamins A and B1 (raised vs normal TGA; vitamin A: 40% vs 17%, p = 0.044, vitamin B1: 37% vs 13%, p = 0.028). Low vitamin A (p = 0.009) and vitamin D (p = 0.001) were more common in samples collected during winter. There were no associations between micronutrient status with GIP, body mass index, height, socioeconomic status, or gastrointestinal symptom. Multivitamin use was less common in patients with low vitamin D. Conclusions: Several micronutrient deficiencies in CD respond to a GFD but others need to be monitored long-term and supplemented where indicated.